Kolaborasi Strategis Dan Tata Kelola Inklusif Untuk Akselerasi Ekosistem Perekonomian Syariah Nasional - Lisa Wahyuni (Indonesia Economic Journal, 2025)
Indonesia, as the country with the largest Muslim population in the world, holds crucial potential to become a global hub for the Islamic economy. However, accelerated growth is hampered by the challenges of fragmentation between the Islamic finance sector and the real halal industry, as well as by governance that is not yet fully integrated. This study aims to analyze a multi-stakeholder collaboration model involving the government, industry, academia, and communities that is effective in bridging this gap. The method used is a policy-based literature review and a synthesis of case studies of successful collaborations at the national and regional levels. Key findings indicate that the Islamic economy requires governance capable of aligning the ecosystem, supported by the integration of Islamic Fintech as a catalyst. Structured collaboration, particularly within the Blended Finance scheme, is crucial for creating a resilient and sustainable ecosystem. A key recommendation is the establishment of a Digital Sharia Task Force to facilitate cross-sector data and policy integration.